The application of WAQF in Medieval Syria : a historical survey during the period of Sultan Nur Al-Din (1146 - 69) and Sultan Salah Al- Din (1169 - 93) - Burhan Che Daud (Universiti Malaysia Kelantan, 2015)
Waqf (pl. awqaf) is an important economic instrument in the context of Islamic society and tradition. It is usually termed in English as Islamic religious or pious endowment. According to Monzer Kahf, in the Islamic law, the word waqf implies the sense of holding certain property and preserving it for the confined benefit of certain philantrophy and prohibiting any use or disposition of it outside its specific objectives. Historical narratives show that the execution of waqf in Islam began during its formative years. The first general religious waqf in Islam initiated by Prophet Muhammad himself through the establishment of Qubā’ mosque and the erection of the Prophet’s mosque in Medina six months later. However, according to ‘Abd Allāh ibn Ahmad al-Zayd, the earliest waqf khayrī (philantrophic waqf) was the endowment of the Prophet by designating seven orchards acquired through the will of a Jewish resident in Medina, Mukhayrīq, after he was killed in the battle of ‘Uḥud